Evaluation of blocking constraints for survivable WDM optical networks - Suthaharan, S.; Sharfana, F.A.; Thiruvanantharajah, S. (IEEE International Conference on Industrial and Information Systems (ICIIS), 2017)
The advantage of a huge amount of data transmission in form of multimedia broadband services can be benefited using a technique called wavelength division multiplexing (WDM) technology. In WDM, the huge amount of bandwidth can be divided on a fiber in several non-overlapping wavelength channels simultaneously. In case of failure in optical networks, vast amount of data will be lost due to some reasons such as fiber-cut. Protection is one of the survivability methods to overcome such failures. We consider dedicated protection in this paper in which primary paths and their associated backup paths are configured at the time of connections establishment. We suppose that a failure on a primary path, the traffic is rerouted through backup path without any configuration as the backup paths are pre configured, therefore, dedicated protection provides the benefit of short recovery time. In this paper, we investigate the performance caused by various constraints in terms of blocking probability for dedicated protection in WDM networks. To evaluate the constraints for blocking probability we deploy various algorithms. In this paper, we carry out the investigation with detailed simulation experiments on different data rates in a standard NSFNET network topology. Findings of our investigation are as follows. (1) Blocking caused by the lack of backup paths is comparatively higher. (2) In certain algorithm, blocking caused by the lack of primary path is higher and considerable. (3) Two algorithms show the same pattern in all the constraints of blocking. (4) Blocking caused by the lack of primary resources and the lack of backup resources are negligible when using all the algorithms.
Keywords: optical networks; dedicated protection; locking constraints; lightpath assignment